Imparting ultralow lubricity to double-network hydrogels by surface-initiated controlled radical polymerization under ambient conditions. (June 2021) - Zhang, Kaihuan; Simic, Rok; Spencer, Nicholas D.
Abstract: Hydrogels, especially double-network hydrogels, are attractive candidates as load-bearing biomaterials, e.g., tissue-engineering supports for articular cartilages and bones. In this study, we describe the modification of a double-network hydrogel by the introduction of a third monomer, N -[3-(dimethylamino)propyl]methacrylamide, to the network system, which serves as a reactive site for subsequent interfacial reactions and surface-initiated controlled radical polymerization under ambient conditions. The as-prepared poly(2-(methacryloyloxy)ethyl trimethylammonium chloride) (PMETAC) polyelectrolyte polymer brush-modified DN hydrogel exhibited an ultralow coefficient of friction (0.001–0.004) under high contact pressure—comparable to that of the synovial joint. Highlights: A high-modulus, double-network hydrogel with a cartilage-mimicking, highly lubricious polymer-brush coating. µ for a PMETAC brush-covered PAMPS/P(AAm-DMAPMA) double-network hydrogel against glass in water is 0.001-0.004 (1-10 N load). A large variety of different polymer brushes can be grown from a PAMPS/P(AAm-DMAPMA) DN hydrogel under ambient conditions.